Peran Komunikasi Antar Budaya dalam Membangun Hubungan Internasional: (Studi Kasus Diplomasi) - Arni Damayanti; Fika Fitriani; Bunga Citra Lestari; Irma Pramudhita; Rapih Nur Kharismatika; Khairunnisa Karimah; Eko Purwanto; Tantry Widiyanarti (Federalisme: Jurnal Kajian Hukum dan Ilmu Komunikasi, 2024)
In the era of globalization, intercultural communication (ICC) is key in building and strengthening international relations. This study aims to explore the role of ICC in the context of diplomacy, focusing on cultural differences that affect communication between diplomats during international negotiations. Through a qualitative approach and case study method, data were collected from in-depth interviews with diplomats and analysis of official documents. The results of the study indicate that cultural differences can cause miscommunication and tension that impact the outcome of the agreement. Therefore, effective communication strategies, such as adjusting communication styles, empathy, and using mediators, are needed to overcome these challenges. With a deep understanding of the cultural background of partners, diplomats can create a constructive communication environment, increase trust, and reach mutually beneficial agreements. This study is expected to provide valuable insights for practitioners, academics, and policymakers in improving the effectiveness of ICC at the international level.